A Social Assay on Bargur Cattle Farming System in Tamil Nadu - Kavithaa, N. V.; Rajkumar, N. Vimal; Mathialagan, P. (International Journal of Livestock Research, 2019)
A study was carried out in Bargur village Panchayat at Anthiyur Block of Erode District in Tamil Nadu to assess the socio personal profile, Bargur cattle rearing system and to ascertain the socio- cultural, economic and psychological impact of Bargur cattle on the herder’s life. Thirty farmers owning Bargur cattle herd were purposively selected as respondents. A well-structured pre tested interview schedule was used to collect the data on profile of the sample respondents and data were collected during June 2018. Focused group discussions, personal interviews and RRA techniques were employed to document the traditional as well as scientific management practices followed by the Bargur cattle farmers. The findings indicate that majority of the respondents belonged to middle to old age group (86.70 %) with primary level of education (46.0 %). Majority of the respondents were marginal to small farmers with an average annual income of less than Rs. One lakh. Majority of the animal houses were of mud flooring with no roof and the animals were grazed for 8 to 10 hours along with additional green fodder during dry season. Almost all the respondents expressed that rearing of Bargur cattle has created a substantial increase in their economic status and 83.33 per cent of the respondents stated that their self-confidence was increased to some extent as they are engaged in traditional farming which is well known to them and also, they are conserving the valuable breed. It was found that majority of the farmers maintain this breed as a traditional practice for livelihood, agriculture and draught purpose. Hence, programmes should be made in such a way that by involving the local community for conservation of the breed and also to get more returns from the existing system of livestock farming thereby enhancing the livelihood of the farmers.